Woke up this morning : the definitive oral history of The Sopranos - Imperioli, Michael, 1966-; Schirripa, Steven R. (William Morrow, an imprint of HarperCollinsPublisers, 2021)
Expanding on the Talking Sopranos podcast with exclusive interviews with the cast, crew, producers, writers, directors, and, of course, the series creator David Chase, stars Michael Imperioli and Steve Schirripa will cover the entire history of The Sopranos series from the original concept pitch and casting to the infamous cut to black - and answer many of the thousands of fan questions sent to the podcast, as well as dispel some widely propagated myths and reveal things no one outside the show would even know to ask. Print run 100,000.